BIOACTIVITY OF ESSENTIAL OILS FROM MEDICINAL PLANTS OF CAMEROON AND THEIR COMBINATION AGAINST INFANT DIARRHEA INDUCED BY BACTERIA - Ascension, Nyegue Maximilienne; Del Florence, Moni Ndedi Esther; Florentine, Ndoyé-Foe; Fronçois-Xavier, Etoa; Menut, Chantal (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: In Cameroon, one of the most common childhood illnesses after malaria is diarrhea, which generally has a bacterial origin. In rural areas, plant utilization is often one of the first ways of treatment though, with no scientific bases. Therefore, the aim of this work was to evaluate the antibacterial activities of nine essential oils (EOs) of Cameroonian plants and their combinations against some strains responsible for diarrhea. Material and Methods: To determine the bacterial species generally involved in childhood diarrheal infections, a retrospective study was done. The EOs of Eucalyptus globulus, Cymbopogon citratus, Xylopia aethiopica, Thymus vulgaris, Ocimum canum, Cananga odorata, Citrus medica, Citrus paradisi and Citrus reticulata were screened against the most incriminated bacterial species using the spot-on-agar test and microdilution methods. Some of the EOs with good antibacterial activity were analyzed by Gas Chromatography and Gas Chromatography/Mass Spectrometry. According to their composition, Thymus vulgaris and Eucalyptus globulus EOs were combined with that of Cymbopogon citratus using the ratios 2/1; 1/1; 1/2 (w/w) and tested against on bacterial growth. Results: The retrospective study showed that 10.8% of infant diarrhea was caused by Escherichia coli, Salmonella typhimurium and Salmonella paratyphimurium. The Minimum inhibition Concentrations (MIC) of single EOs was between 0.78 and 25 mg/mL which were observed to be greater than those of their combinations which ranged between 0.195 and 6.52 mg/mL. The active essential oils contained mainly hydrocarbonated and oxygenated monoterpens. Conclusion: The good antibacterial effects of two Thymus combinations Th1 and Th2 observed on Salmonella typhimurium and Salmonella paratyphimurium suggest their used in aromatherapy to cure bacterial diarrhea.